Bound and Gagged : Pornography and the Politics of Fantasy in America - Kipnis, Laura (Book collections on Project MUSE., 1999)
Presents and challenges the most basic assumptions about America's relationship with pornography and questions what the calls to eliminate it are really attempting to protect.